The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijerph20075338
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Risks of BMI and Health-Related Lifestyles on Kidney Function in the Prediabetic Japanese Population: A Prospective Cohort Study

Abstract: Diabetic overweight patients are more likely to show the progression of kidney damage than the general population. The majority of people in the early stages of kidney damage do not recognize the importance of risk modification, mainly due to the asymptomatic nature of the disease. This study aimed to examine specific risk combinations of lifestyle and BMI regarding the deterioration of kidney function and to explore whether there are gender-based differences among the prediabetic population. Prediabetic parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“… 9 , 10 , 11 , 12 , 13 , 14 A prospective cohort study in Japan concluded that smoking, snacking, irregular exercise, and sleep deprivation accelerate the progression of kidney injury in the male population with diabetes. 15 Previous studies have also shown that vegan and low‐salt diets can prevent DKD and its progression. 16 , 17 A Mendelian randomization study found that short sleep duration had a detrimental effect on kidney function.…”
mentioning
confidence: 99%
“… 9 , 10 , 11 , 12 , 13 , 14 A prospective cohort study in Japan concluded that smoking, snacking, irregular exercise, and sleep deprivation accelerate the progression of kidney injury in the male population with diabetes. 15 Previous studies have also shown that vegan and low‐salt diets can prevent DKD and its progression. 16 , 17 A Mendelian randomization study found that short sleep duration had a detrimental effect on kidney function.…”
mentioning
confidence: 99%